Predicting degradation of organic molecules in cementitious media. (October 2021) - Bagaria, F.; Riba, O.; Albrecht, A.; Robinet, J.-C.; Madé, B.; Román-Ross, G.
Abstract: Degradation of organic compounds is a key issue in the performance assessment programs for Low and Intermediate Level radioactive Waste (L-ILW) repositories. Despite significant progress in recent decades, parameterization and implementation of biotic degradation of these compounds in reactive transport models still remain a challenging task, mainly due to uncertainties linked to their complex chemical behaviour. In this work we have explored the application of thermodynamic models in order to stablish a predictive kinetic model for nineteen organic molecules of particular interest in the frame of Low and Intermediate Level Waste disposals. Firstly, from a compilation of experimental data taken from the literature, we observed a decreasing trend in the zero-order kinetic degradation rates as the number of carbon atoms increases. Even though this conclusion is based on thermodynamic and experimental data obtained at circumneutral pH conditions, it can be considered as indicators of most probable processes expected at foreseen alkaline storage conditions. Based on the model published by LaRowe and Van Cappellen (2011) for natural organic matter degradation, a set of organic molecules of interest were analysed and compared. This thermodynamic calculations allowed us to classify the molecules of interest in three different groups regarding their most probable behaviour: i) adipate, succinate, pimelate, benzoate, TPB − and DBP − been identified as persistent molecules as their degradation is thermodynamically inhibited and they represent potential radionuclides complexing agents; ii) oxalate, formate, gluconate, lactate, NTA −, propionate, acetate, ISA- and sorbate will be easily oxidized and their kinetic degradation will proceed while the substrate for bacterial growth remain available. A third group can be mentioned and comprises organic molecules having a partly inhibited degradation from the thermodynamic point of view (DBP − EDTA −, DTPA − ). Different biodegradation pathways are mentioned in the literature for these molecules. Given the high complexity of the involved processes, more experimental studies are needed before concluding on their availability for microbial processes.